2005
DOI: 10.1136/pgmj.2004.027532
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial infarction in young adults

Abstract: Although myocardial infarction (MI) mainly occurs in patients older than 45, young men or women can suffer MI. Fortunately, its incidence is not common in patients younger than 45 years. However, the disease carries a significant morbidity, psychological effects, and financial constraints for the person and the family when it occurs at a young age. The causes of MI among patients aged less than 45 can be divided into four groups: (1) atheromatous coronary artery disease; (2) non-atheromatous coronary artery di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
163
0
30

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(197 citation statements)
references
References 56 publications
4
163
0
30
Order By: Relevance
“…Coronary angiography (CAG) more often shows normal coronary arteries, prompting for a search for non-atherosclerotic aetiology such as coronary spasm, vasculitis, embolism, or hypercoagulability. In young and very young subjects, destructive lifestyle factors have also been highlighted, including exaggerated ambitions, competition, workaholism, poor diet, use of psychoactive substances including cocaine, marijuana, and anabolic steroids, and disregarding early disease symptoms [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Coronary angiography (CAG) more often shows normal coronary arteries, prompting for a search for non-atherosclerotic aetiology such as coronary spasm, vasculitis, embolism, or hypercoagulability. In young and very young subjects, destructive lifestyle factors have also been highlighted, including exaggerated ambitions, competition, workaholism, poor diet, use of psychoactive substances including cocaine, marijuana, and anabolic steroids, and disregarding early disease symptoms [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Se han descrito una serie de mecanismos por los cuales el uso de cocaína puede llevar a un IAM, dentro de los cuales se encuentran el vasoespamo coronario y un estado de hipercoagulabilidad 13 . Del mismo modo, el uso prolongado de esta droga también se ha asociado a fenómenos de aterosclerosis acelerada, por lo que no debiera extrañar la presencia de placas ateroscleróticas accidentadas en estos pacientes 14 . Al igual que en otras experiencias, encontramos que los pacientes jóvenes con IAM presentan menor carga de enfermedad coronaria, con Score de Syntax bajo y enfermedad de un vaso predominante (4,7).…”
Section: Discussionunclassified
“…It has been shown, for example, that sex hormones can also dictate the expression of extracellular matrix and MMPs in the aorta [8,27]. The fact that the gender difference in the incidence of MI disappears after menopause [3] also supports this notion. In addition, it has been shown that the hormonal pattern directly affects ventricular remodeling after MI.…”
mentioning
confidence: 86%
“…The Framingham study, for example, has demonstrated that the incidence of acute MI is 2.5-fold higher in males than females before age 45, however, this gender difference disappears after 55 years of age [3]. Clinical studies indicate that the rate of acute mortality, including sudden death, in men is about twice that observed in women [4].…”
mentioning
confidence: 99%